Comunidade de bactéricas endofíticas de Paullinia cupana var. sorbilis (Mart.) Ducke e seu potencial biotecnológico - Liotti, Rhavena Graziela (2017)
Endophytic bacteria can synthesize potentially beneficial metabolites for their host, stimulating plant growth, resistance to abiotic stresses, or protection against phytopathogen attacks. Plants of high biodiversity environments may harbor endophytes with abilities to promote the best performance of the host in these areas of high plant endemicity. Guarana is an Amazon plant of economic and social importance due to the high caffeine content of its seeds. An interesting approach in the search for endophytic microorganisms with potential biotechnological application is to understand the factors that influence the endophytic community to rationalize host management programs. In this study we used traditional culturing techniques as well as next-generation sequencing (NGS) for 16S rRNA gene of bacteria to understand the influence of plant site, genotype and organ in the community of endophytic bacteria of P. cupana. We studied the potential of endophytic actinobacteria of P. cupana as antimicrobial agents of agricultural phytopathogens, as well as their extracts. By the technique of cultivation we obtained a lineage bank with 95 species distributed among 29 genera and 3 bacterial phyla (Proteobacteria, Actinobacteria and Firmicutes). The organ of the plant influenced the bacterial community in CT, richness, diversity and species composition. The site and the genotype influenced the composition of species. Among the communities there are lines with important traits of promotion of growth and antagonism against the main phytopathogens of guaraná, however these communities are not separated by functional traits. The application of the main strains for growth promoting traits promoted growth in Sorghum bicolor. Based on 289,468 sequences, 6,349 Operational Taxonomic Units (OTUs) were distributed in 34 phyla, 116 classes, 227 orders, 430 families, 818 genera and 1343 species. P cupana is abundantly colonized by Proteobacteria, Firmicutes, Actinobacteria and Bacteroidetes, and specifically with relative high frequency of the genera Streptococcus and Acidothermus in leaves and roots, respectively. Indicator OTUs between sites (9 OTUs), genotypes (11 OTUs) and organs (11 OTUs) were observed. The organ of the plant influenced the endophytic community both in the richness, diversity, composition of OTUs, relative abundance of phylum and genus, as well as in the network of interaction between species. However, the site and genotype of the plant influenced the composition and interactions of the species in the network analysis. We did not observe variations in the physiological profile of endophytic communities obtained from different localities and genotypes. We selected 11 species of actinobacteria for antibiosis testing. Streptomyces griseocarneus R132, Streptomyces prasinopilosus R199 and Streptomyces acidiscabies R403 showed antibiosis in vitro against Colletotrichum guaranicola, Fusarium decencellulare, Botryosphaeria dothidea, Colletotrichum gloeosporioides and Fusarium oxysporum. S. griseocarneus R132 showed the highest values of inhibition of phytopathogens, varying from 73.93% for B. dothidea, to 57.24% for F. oxysporum, besides significantly controlling (Kruskal-Wallis, p> 0.05) the development of the symptoms of anthracnose (causative agent C. gloeosporioides) in fruits and plants of Capsicum annuum. The antibiotic was caused by compounds synthesized by the strain S. griseocarneus R132 because the extract obtained from the fermentation of this species was able to inhibit the growth of all phytopathogens evaluated. The application of the extract in the fruits of Capsicum annuum efficiently (T test, p <0.05) controlled the anthracnose symptoms reducing the lesion size by 30%. S. griseocarneus R132 promoted significant growth of C. annuum (T test, p <0.05) in 42% of shoot dry mass. This work reveals important groups of endophytic bacteria in P. cupana and that especially the host organ modulates the structure and interactions in this community. The strain Streptomyces griseocarneus R132 is promising for the biological control of phytopathogens both for pre-harvest and post-harvest and its extracts have substances of interest for new bioprospecting studies. This work opens opportunities to study the application of isolated strains in the bioprospecting of processes and products.